Neurohormonal changes and intestinal barrier function disorders in irritable bowel syndrome in patients with metabolic-associated fatty liver disease and their correction - Sirchak, Yelyzaveta (ScienceRise: Medical Science, 2025)
The study of neuropsychometric disorders in patients with irritable bowel syndrome (IBS) in combination with metabolic associated fatty liver disease (MAFLD) can expand the diagnostic aspects and treatment options for patients with combined pathology. The aim of this study was to evaluate the impact of neurohormone levels and intestinal barrier function disorders on neuropsychometric changes in patients with IBS and MAFLD, as well as their correction. Materials and methods. We examined 60 patients with IBS in the setting of MAFLD. The level of melatonin (MT) and serotonin (ST) in the blood serum was determined. The levels of α1-antitrypsin (α1-AT) and zonulin in the blood serum and faeces of the examined patients were evaluated. Patients were divided into two groups. The first group of patients (n=30) received only basic therapy. The second group of patients (n=30), in addition to the basic treatment, received the symbiotic drug Lothardi-A. The subjects were assessed for central nervous system dysfunction (Spielberg and Khanin self-esteem scale; Beck Depression Scale; Zang scale; Toronto Alexithymic Scale). Research results. The obtained results confirm the positive effect of Lothardi A on improving the permeability of the intestinal barrier and the level of neurohormones in the blood serum in IBS and MAFLD. Additionally, a pronounced positive dynamic in the indicators of neuropsychotrauma is observed in these patients. Conclusions: Changes in the level of ST and MT in the blood serum, which correlate with the severity of intestinal barrier function disorders, were diagnosed in patients with IBS and MAFLD. In patients with IBS and MAFLD, neuropsychometric status disorders were found. The course prescription of Lotardi-A as part of complex therapy for patients with IBS and MAFLD is pathogenetically justified and leads not only to the improvement of clinical symptoms but also contributes to the improvement of dysbiotic changes, impaired intestinal barrier function, normalization of serum levels of ST, MT, which is a prerequisite for improving the mental status of these patients